Growth and Yield Response of Turmeric (Curcuma Longa L.) to NPSB and Urea fertilizer in Yeki District, Southwest Ethiopia - Amante, Guta; Wedajo, Mulisa; Temteme, Shiferaw (International Journal on Food, Agriculture and Natural Resources, 2025)
Besides its significance in human nutrition and being cash crop in Ethiopia, turmeric is produced far below the countries potential, due to the depletion of major soil nutrients. This crop requires adequate fertilizer application. The purpose of this field experiment was to evaluate the effectiveness of the blended NPSB fertilizer indicated by the Ethiopian soil information system (EthioSIS) soil fertility map for turmeric production in the study area. The treatments were laid out in a randomized complete block design with three replications. The treatments included two controls (control and recommended NP fertilizer) and nine combinations of NPSB fertilizer (100, 150, and 200 kg ha-1) and, N fertilizer (Urea) (150, 200, and 250 kg ha-1) arranged in RCBD with three replications. The showed that the applying increased rate of blended NPSB along with urea did not brought significant improvement) in growth and yields components of turmeric over existing treatment groups compared to negative control. The highest fresh rhizome yield (41.52 t ha-1) was obtained from the application of 100 NPSB with 250 urea. Since the blended fertilizer, non-significantly increased turmeric yield, farmers in the study area and similar agro ecologies could use the previously recommended NP fertilizer for turmeric production.